(3GdHRGRjI aj GdaJGhis - (3GdHRGRj, eMeO Hf eMeO Hf TgGH, J (B827 (3g`s ((3eMdjI UGdMjI aj GdTGes)
(3ChdgG (B:s
(3HYO GdHSedI ; cJGH GdOYhi hajg SJi YTQ aUdG GdChd aj eYQaI GdNUe hGdJfGbV hGdOaY heSGFd gPG GdLfS Ydi GdJeGe jPcQ aj GdNGeS YTQ Ef TGA Gddg JYGdi hCdMbG HeSGFd GdNUes
(3BNQgG (B:s
(3aEf UeJ jheG acJH Ch CTGQ HTjA dG ojYJHQ dCfg fGWb HMGdg hEf UeJ HYGQV agh cGdeQjV GdeYJbd dSGfg cPG aj GdeMHhHjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 45s
(3eYLe GdeDdajf (B3 / 646s
(3cTa GdXfhf (B1 / 242s
(3TPQGJ GdPgH (B7 / 183s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs